Prevention and control of infections in the hospital environment: Occupational health and safety - da Silva, Maria Luiza Ferreira Imburana; de Farias, Shirlley Jackllanny Martins; dos Santos , Isadora Sabrina Ferreira; Silva, Maria Graziele Gonçalves; de Oliveira, Emília Carolle Azevedo (Seven Editora, 2024)
Introduction: The correct performance and expanded knowledge of health professionals are essential due to the high incidence and complications of nosocomial infections, which can delay the patient’s recovery and increase the risk of nosocomial infection. This problem is one of the great challenges of public health in Brazil and must be managed competently to ensure patient safety and care in health units. Objective: This study aims to disseminate knowledge and encourage the correct practice of hand hygiene, the proper use of Personal Protective Equipment (PPE) and hospital cleaning, reflecting on health and safety at work in the prevention and control of infections in the hospital environment. Methodology: This is a bibliographic review, of a narrative, exploratory and descriptive nature, based on scientific articles indexed in Google Scholar and in the Virtual Health Library (VHL) platform, using the PubMed and Scientific Electronic Library Online (SciELO) databases. Conclusion: Nosocomial infection represents a major challenge for public health, exposing patients to possible infections caused by bacteria and microorganisms, sometimes acquired due to the patient’s own low immunity and resistance or due to failures in infection control processes and biosafety measures. DOI:https://doi.org/10.56238/sevened2024.025-012